Evaluation of Topical Tocopherol Cream on Cutaneous Wound Healing in Streptozotocin-Induced Diabetic Rats. (14th October 2012) - Lin, Teoh Seong; Abd Latiff, Azian; Abd Hamid, Noor Aini; Wan Ngah, Wan Zurinah bt; Mazlan, Musalmah
Abstract : Diabetes is a common cause of delayed wound healing. The aim of the study was to determine the effect of topical administration of tocopherol cream on the wound healing process in diabetic rats. The study was conducted using 18 male Sprague Dawley rats which were divided into three groups: (I) diabetic rats receiving control cream ( n = 6 ), (II) diabetic rats receiving 0.06% tocopherol cream ( n = 6 ), and (III) diabetic rats receiving 0.29% tocopherol cream ( n = 6 ) . Four cutaneous wounds were created at the dorsal region of the rats. Wound healing was assessed by total protein content, rate of wound closure estimation, and histological studies on the tenth day after wounding. Tocopherol treatment enhanced the wound healing process by increasing rate of wound closure and total protein content significantly ( P < 0.05 ) compared to the control group. Histological observation also showed better organized epithelium and more collagen fibers in the tocopherol treated groups. Application of tocopherol cream enhances wound healing process in diabetic condition which is known to cause delay in wound healing.